UPAYA PENCEGAHAN PENULARAN COVID 19 MELALUI PEMBIASAAN CUCI TANGAN 6 LANGKAH PADA SISWA SD 11 DESA TANJUNG SALEH KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Erwhani, Indri; Hartono; Wuriani; Ariyanti, Sri; Rikayati (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
Hand washing is done to clean hands and fingers from germs that stick to hands and fingers. Germs that stick to human hands and fingers can enter the digestive or respiratory tract and cause disease. Hand washing is an activity that is light to do, even according to some people it is a trivial thing, but it has enormous effects and benefits for health. At school age (4th grade) it is identical to playing time, activities carried out by children tend to come into contact with game tools, thus the risk of children being exposed to microorganisms that cause disease is greater. Introducing good habits to maintain health in school-age children is a challenge for teachers and parents, this is because children in this age group are still not able to think logically. Therefore, they must be reminded and taught repeatedly so that something new can become a habit for them. Activity Targets: The targets in this activity are students and teachers of SDN 11 Tanjung Saleh, Sungai Kakap sub-district, Kubu Raya district, West Kalimantan. Evaluation: This Abdimas activity has formed good habits for the students of SDN 11 Tanjung Saleh as an effort to prevent the transmission of the Covid 19 virus with the result that 73.3% of participants were able to do it independently and 26.7% were still being helped to wash their hands properly in 6 steps. This is an increase from before the counseling and demonstration was carried out in which 43.3% could do it independently and 56.7% were assisted.